1939
DOI: 10.1139/cjr39c-005
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON POLYMYXA GRAMINIS, N. GEN. N. SP., A PLASMODIOPHORACEOUS ROOT PARASITE OF WHEAT

Abstract: A new member of the Plasmodiophorales with rather unusual characteristics has been found parasitizing the roots of wheat grown in soil from three different localities in Ontario. In addition to spore clusters of the Ligniera type, large, septate zoosporangia with conspicuous tubes for zoospore discharge are present. These multinucleate zoosporangia are produced by progressive lobular outgrowths from uninucleate amoebae and from the beginning are always surrounded by a thin wall. In the formation of resting spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…Optimal activity of P. graminis from temperate locations has been shown to occur at or near 15°C (Legreve et al 1998). Cycling wet and dry periods, as seen in 2000, have been shown to favour the growth of P. graminis (Adams et al 1986), whereas prolonged periods of wetness have been shown to reduce spread (Ledingham 1939). In addition, Cadle-Davidson et al (2003) have shown no significant transmission of Soil-borne wheat mosaic virus (SBWMV), a close relative of Cultivars are ordered by increasing yield.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Optimal activity of P. graminis from temperate locations has been shown to occur at or near 15°C (Legreve et al 1998). Cycling wet and dry periods, as seen in 2000, have been shown to favour the growth of P. graminis (Adams et al 1986), whereas prolonged periods of wetness have been shown to reduce spread (Ledingham 1939). In addition, Cadle-Davidson et al (2003) have shown no significant transmission of Soil-borne wheat mosaic virus (SBWMV), a close relative of Cultivars are ordered by increasing yield.…”
Section: Discussionmentioning
confidence: 98%
“…Both SBCMV and WSSMV are vectored by Polymyxa graminis (Ledingham 1939), a soil dwelling protist able to survive and remain infective in soil for over a decade (Kendall and Lommel 1988). Cultivars vary in susceptibility to each virus; some cultivars have been shown to have low virus titre in leaf material, mild or no symptoms, and little or no yield penalty when grown on virus-infected land, and therefore offer a practical method for disease management.…”
mentioning
confidence: 99%
“…Polymyxa graminis (Ledingham, 1939) and P. betae (Keskin, 1964) are examples of species which can act as vectors of significant pathogenic soil-borne viruses, for example, Soil borne cereal mosaic virus (Brakke, 1971) and BNYVV (Fujisawa and Sugimoto, 1976). Although these particular viruses are no longer of statutory concern to the UK, their vectors are still likely to be of quarantine concern in the future as resistance-breaking strains of current viruses or new viruses appear.…”
Section: Polymyxa Speciesmentioning
confidence: 99%
“…Several researchers have carried out morphological observations of these fungi with light microscopes or transmission electron microscopes (TEM) (Barr, 1979;Barr and Asher, 1996;D'Ambra and Mutto, 1977;Keskin, 1964; Keskin and Fuchs, 1969;Langenberg and Giunchedi, 1982;Ledingham, 1939). However, scanning electron microscopy (SEM) was employed in only a few studies Marotta, 1988, 1989) due to the difficulty in preparing suitable specimens.…”
Section: Introductionmentioning
confidence: 97%